The life of David Gale [videorecording (DVD)] - Parker, Alan, 1944-2020-; Spacey, Kevin; Winslet, Kate; Linney, Laura; McCarthy, Melissa, 1969- (Universal, 2003)
A reporter is sent to chronicle the last days of an anti-death penalty activist now living on death row, after having been convicted of the murder of a fellow activist. The reporter grows to suspect he may have been framed, and sets out to verify her doubts.